Behavioral reaction to amyloid beta status disclosure. (20th December 2022) - Lesman‐Segev, Orit H.; Golan, Sapir; Zadok, Maya; Kishenevsky, Sarah; Ben‐Meir, Mery; Bem‐Moshe, Ariela; Heymann, Anthony; Azuri, Joseph; Ravona‐Springer, Ramit; Hoffmann, Chen; Domachevsky, Liran; Beeri, Michal Schnaider
Abstract: Background: Limited information exist regarding the reaction of cognitively unimpaired research participants to amyloid status disclosure and even more so in observational studies. We aimed to assess the associations of amyloid status disclosure with reported subjective memory concern, motivation to change lifestyle, anxiety, and depression. Method: Research participants that take part in two observational studies and two clinical trials that incorporate amyloid‐PET where included. Participants received information regarding amyloid‐PET testing, results, and interpretation. They then performed an interview prior to PET scan and four‐to‐six‐month following result disclosure assessing their subjective memory concern, motivation to change lifestyle, anxiety, and depression from the possibility of a positive amyloid‐PET result. Result: 130 cognitively normal adults completed both the pre‐PET and post‐PET questionnaires. Only 11 had a positive amyloid‐PET result and thus were excluded from the analyses. Of the 119 subjects with a negative PET scan, 70 (59%) were females, mean age = 62Y (rang 44‐88Y), mean education = 16Y (4‐25), mean MMSE = 29 (24‐30); most (64%) reported no memory concerns or mild memory concerns (1/2 on a scale of 5). This increased to 94% at 4‐6 month following amyloid‐PET disclosure (Figure 1 ). Most (84%) had high or very high motivation to change lifestyle (4/5 in a scale of 5) in the pre‐PET assessment. This decreased to 30% in the post‐PET assessment. High and very high (4/5 in a scale of 5) anxiety and depression from a positive amyloid scan rates decreased from 25% to 0% and from 10% to 0%, respectively following a negative PET result disclosure (Figure 1 ). Although most individuals reported favorable post‐PET changes, a few subjects experienced increase in memory decline (N = 8), anxiety (N = 6) or depression (N = 1) following disclosure (Figure 2 ). Conclusion: In cognitively normal adults, the disclosure of a negative amyloid‐PET scan result was associated with a general "comforting" effect as reflected by less subjective memory concerns, anxiety, and depression, and lower motivation to perform lifestyle changes. By AAIC 2022, we anticipate more participants who are amyloid‐PET positive allowing to compare their behavioral changes after disclosure of amyloid results to the changes of those who are amyloid‐PET negative.